2005
DOI: 10.1097/01.pgp.0000148338.84887.08
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Detection of Human Telomerase Reverse Transcriptase (hTERT), Topoisomerase II?? Expression, and Apoptosis in Endometrial Adenocarcinoma and Atypical Hyperplasia

Abstract: This study evaluated the immunohistochemical expression of human telomerase reverse transcriptase (hTERT) in endometrial carcinoma and atypical endometrial hyperplasia, and related it to the expression of topoisomerase (TP)IIalpha (a proliferation associated enzyme); apoptosis as determined by the frequency of apoptotic bodies (ABI); mitotic counts; and other clinicopathologic variables. Immunoreactivity for hTERT and TPIIalpha as well as ABI were assessed in 57 endometrial samples (12 atypical hyperplasias, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
2
10
0
1
Order By: Relevance
“…Telomerase activity was determined to be between 14.2% and 80% in premalignant endometrial tissue samples, and the positivity rate was generally higher in lesions with cellular atypia (15,17). There was no premalignant endometrial sample in this study, but the results of a study conducted among the Turkish population were parallel with current literature published in the English language (18).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Telomerase activity was determined to be between 14.2% and 80% in premalignant endometrial tissue samples, and the positivity rate was generally higher in lesions with cellular atypia (15,17). There was no premalignant endometrial sample in this study, but the results of a study conducted among the Turkish population were parallel with current literature published in the English language (18).…”
Section: Discussionsupporting
confidence: 79%
“…In this study, all six malignant endometrial tissue samples (100%) were found to be positive for hTERT. The positivity rate of telomerase activity in endometrioid adenocarcinoma was reported to be between 70% and 100% in previous studies (15,17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown significant overexpression of p53, Ki-67, and human telomerase reverse transcriptase (TERT) in invasive and non-invasive uterine serous carcinoma. [5][6][7][8] The current study evaluates the expression of p53, Ki-67, and TERT in atypical tubal metaplasia, and the usage of these immunohistochemical markers in differentiating this metaplasia from intraepithelial or invasive uterine serous carcinoma. This study also uses long-term follow-up to evaluate the risk of subsequent endometrial neoplasia associated with atypical tubal metaplasia.…”
mentioning
confidence: 99%
“…Topo IIa, with a molecular mass of 170 kDa, is expressed in proliferating cells in the late S phase with a peak in G2-M phases [9] . Inhibition of topoisomerases promotes cell death and for this reason they are targets for specific chemotherapy [10][11][12] . Topo IIa inhibitors, such as anthracyclines, are used as adjuvant chemotherapy combined with other agents (gemcitabine) in PDAC [13,14] .…”
Section: Introductionmentioning
confidence: 99%